The Expert System Detects Early Symptoms Of Cholesterol Disease With Certainty Factor Method At Lubuk Pakam Puskesmas - Muhammad Afriandi; R. Magdalena Simanjorang (Putaka Timur Publisher, 2021)
Cholesterol is one of the components that can form fat contained in the bloodstream or body cells that are directly needed in the formation of cell walls. The components of triglycerides, phospholipids, free fatty acids, and cholesterol are found in fat. The method used in this research is the Certainty Factor. The certainty factor expresses belief in an event (fact or hypothesis) based on evidence or expert judgment. Identification of the problem in this study is the limited working hours of experts or doctors and expensive consultation fees Making this application discusses the Certainty Factor method using the Visual Basic 2010 application. The benefit of an expert system for detecting cholesterol disease is that people with cholesterol disease can find out information about cholesterol disease. If there are symptoms that arise, patients can do and find out for themselves without having to wait in line for a consultation with a doctor.